AN UNUSUAL DIAGNOSIS OF PINPOINT TONIC PUPILS. Issue 10 (9th September 2014) - Mihalova, Tatiana; Jackson, Susan; Verghese, Priyam
Abstract : A 65 year old female presented following 2 weeks of coryzal symptoms with subacute diplopia and ataxia limiting her mobility. She noticed left hand paraesthesia, spreading over 2 days to both upper limbs and face. Examination revealed bilateral ptosis (no evidence of fatigability), miotic tonic pupils with complete ophthalmoplegia, total areflexia and patchy loss of vibration sense in both upper and lower limbs. Power was normal throughout. Proprioception and sensation to light touch were intact. In the peripheral hospital MRI brain and CSF examination were unremarkable. Tensilon test was negative. She was started on intravenous immunoglobulins on day 5 of admission and transferred to a tertiary neurology centre. Neurophysiology tests revealed no abnormality. Anti GD1B, GT1B, GQ1B IgG were positive in high titres (1:>12500). This case illustrates an interesting pupillary involvement in Miller-Fisher syndrome (MFS). Early use of immunotherapy was instituted and the patient made a rapid recovery (over 3 days). Current evidence for the use of immunotherapy in MFS is limited to case-series. Research suggests a pathogenic involvement of anti-ganglioside antibodies, thus proposing treatment aimed at their removal. This case lends support to immunotherapy for the treatment of MFS; further evidence is required to assess its efficacy.